Avaliação da qualidade do leite e caracterização de laticínios do estado do Espírito Santo - Tonini, Christyane Bisi (2014)
Milk is a food of great importance in human nutrition and widely consumed. Thus, it is justified to study its characteristics and evaluate hygienic procedures during the entire production chain, from milking to processing. The objective of this work was to characterize the dairy companies located in the state of Espírito Santo, and measure the quality of raw milk and pasteurized milk from four establishments. The study was divided into four stages: 1) Selection of two dairy companies with Seal Federal Inspection (SIF) and two dairy companies with Seal of State Inspection (SIE); 2) Development of questionnaire for data collection; 3) Sampling of refrigerated raw milk and pasteurized milk at the selected dairy companies and evaluation of the quality of the milk samples and; 4) Characterization of the four companies and evaluation of their sanitary conditions (administration of the questionnaire and application of the check-list present in the RDC No 275/2002 of ANVISA). Results showed that chemical composition, titratable acidity, pH and somatic cell count (SCC) samples of companies SIF 1, SIF 2, SIE 1 and SIE 2 were in accordance with the standard required by MAPA's Instruction N. 62/2011. All samples presented staining reddish brown / pink and no clotting as to alizarol test, indicating compliance with the requirement of the legislation. Concerning the test of detection of ß-lactam antibiotic, all milk samples were absent according to the used method. In one of the analyzed samples, referring to a repetition of the company SIF 1, it was verified the presence of alkaline phosphatase enzyme in pasteurized milk, indicating that the treatment was not appropriate or the enzyme renatured, which would lead to a false positive result for the test. It was found that both samples of milk collected from a company with SIS showed absence of lactoperoxidase, indicating its superpasteurization due to denaturation of the enzyme. Regarding microbiological analyses of total bacterial count (TBC), mesophilic and psychrotrophic bacteria, results were higher than expected according to legislation. In addition, higher values for total bacterial count, psychrotrophic coliforms were found in raw milk samples collected from companies with SIF, probably due to the use of community tanks by producers, longer transportation period when comparing to companies with SIE and greater volume of milk collected from different milk producers. With respect to total bacterial count and total coliform count in pasteurized milk, the highest average values were recorded from companies SIF 1 and SIF 2. Dairy companies that showed higher percentages of adaptation to requirements of GMP were SIF 1 (87.82%) and SIF 2 (80.66%), which either had already implemented or was in the final stage of implementation of Standard Operating Procedure (SOP), GMP and Integrated Pest Management (IPM). Results of microbiological analyses, check-list application, and questionnaire administration allowed us to draw the conclusion that companies with SIF, although showed higher percentage of adequacies to GMP requirements, showed lower raw material quality comparing to companies with SIE. These results demonstrated that the study of dairy companies in the state of Espírito Santo enabled dairy industry and its problems knowledge, contributing to the appliance of improvement action and prevention of future problems.